Repair bond strength of nanohybrid composite resins with a universal adhesive - Pinar Altinci; Murat Mutluay; Arzu Tezvergil-Mutluay (Medical Journals Sweden, 2018)
Objective: To investigate the repair bond strength of fresh and aged nanohybrid and hybrid composite resins using a universal adhesive (UA). Materials and methods: Fresh and aged substrates were prepared using two nanohybrid (Venus Pearl, Heraus Kulzer; Filtek Supreme XTE, 3 M ESPE) and one hybrid (Z100, 3 M ESPE) composite resin, and randomly assigned to different surface treatments: (1) no treatment (control), (2) surface roughening with 320-grit (SR), (3) SR + UA (iBOND, Heraus Kulzer), (4) SR + Silane (Signum, Ceramic Bond I, Heraeus Kulzer) + UA, (5) SR + Sandblasting (CoJet, 3 M ESPE) + Silane + UA. After surface treatment, fresh composite resin was added to the substrates at 2 mm layer increments to a height of 5 mm, and light cured. Restored specimens were water-stored for 24 h and sectioned to obtain 1.0 × 1.0 mm beams (n = 12), and were either water-stored for 24 h at 37 °C, or water-stored for 24 h, and then thermocycled for 6000 cycles before microtensile bond strength (µTBS) testing. Data were analyzed with ANOVA and Tukey's HSD tests (p = .05). Results: Combined treatment of SR, sandblasting, silane and UA provided repair bond strength values comparable to the cohesive strength of each tested resin material (p < .05). Thermocycling significantly reduced the cohesive strength of the composite resins upto 65% (p < .05). Repair bond strengths of UA-treated groups were more stable under thermocycling. Conclusions: Universal adhesive application is a reliable method for composite repair. Sandblasting and silane application slightly increases the repair strength for all substrate types.